Ular Tangga Edukatif : Permainan Edukatif Pencegahan Stunting Di SD Negeri 6 Sumbawa Besar - Rusmayadi Rusmayadi; Lina Eta Safitri; Julia Mujahadah Pratiwi; Raudatul Umroh (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2023)
One of the main tasks of the public health extension functional position that has been established by the Indonesian Ministry of Health in 2008 is to disseminate information and create media designs. The expertise of health educators in information dissemination and media design is very important in influencing public education. The purpose of this service is to increase elementary school students' knowledge about stunting prevention and to involve STIKES Griya Husada Sumbawa students in these counseling activities. The method of implementation is to carry out a stunt-themed Snakes and Ladders game competition for students in grade 6 or grade 5 at Public Elementary School 6 Sumbawa Besar. To measure participants' knowledge of stunting, it was measured using a pretest and post test with a question and answer technique and light discussion. when the presenter hasn't explained the students don't really understand the true meaning of stunting, about 20% of the children's understanding before we explain first. after we explain, finally the children understand or understand about 80% of students